Local government and the provision of low-cost housing in South Africa - Jabulisiwe, N. Ntombela; Nokukhanya, N. Jili (Penerbit Universiti Kebangsaan Malaysia, 2020)
The provision of housing in South Africa is a highly contested social issue which has filtered into the new democracy posing major challenges for policy makers. The colonial and apartheid spatial planning solidified racial and socio-economic segregation in the non-white settlements throughout South Africa. Such unfavourable spatial inequalities are still felt today. Measures of rectification put in place under the new democracy took cognisance of the human rights and social needs they are entitled to as citizens in the restoration of human dignity to the previously disadvantaged while also advocating for equality. Therefore, this article presents an overview of the role of local government in the provision of low-cost housing. Desktop analysis was used to analyse the role of local government in the provision of low cost housing in South Africa. The results of this paper shows that approximately more than 49.2 % of the adult population are living below the upper hand-bound poverty line in South Africa as many people depend on government for almost every need including housing. It is therefore becoming a continuous struggle for government to provide adequate housing to the indigent due to inadequate amount of resources, while the rapid growth in population exacerbates challenges concerning service delivery. This article concludes by indicating that in order to set feasible, reasonable and viable targets, municipalities need to have a good overview of the housing demand. This does not only include the number of houses that are needed, but also the types of houses, their locations, access to basic services and so forth, hence the essential social needs evaluation to be conducted to promote the enhancement of quality of standard of living and the constitutional rights of all the residents.